Emotions and Sentiments in the Process of Political Socialization: a Study from the History of Education - Somoza Rodríguez, Miguel; Mahamud Angulo, Kira; Pimenta Rocha, Heloisa Helena (Historia y Memoria de la Educación, 2015)
The current historical-educational research responds to the affective turn in the sciences too by incorporating emotions and sentiments as categories of analysis and variables to consider in the processes of teaching, learning, acculturation and socialization. The evidence that they play an active role in cognitive, evaluative and axiological processes and in the formation of individual and collective identities, forces historians of education to examine their sources, contexts, subjects and phenomena paying attention (or at least not ignoring or underestimating) these components of the life experience of all human beings in their personal and social dimensions. The introduction to the special issue provides an overview of the historical development of research on emotions and sentiments focusing mainly on psychology, sociology and neuroscience, mentioning its importance in literature, art and politics, to finish deepening in the social feelings that are involved, influence, shape and are shaped (or constructed, incited, provoked, imposed, suggested...) in the processes of political socialization. Formal, non-formal and informal education, at different times and historical contexts, has been the prime mode of transmission of sociopolitical cultures impregnated with a heterogeneous but unavoidable emotional charge. The articles of the special issue evince through the variety of documentary sources, countries, periods and themes how emotions and sentiments -either being intentionally implemented or simply acting in the phenomena of political socialization- are core elements, and therefore carriers of relevant information, in configuring communication resources, teaching strategies and educational aims.